2021
DOI: 10.33448/rsd-v10i11.19195
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade físico-química e microbiológica de salsichas do tipo hot dog na cidade de Mossoró, Rio Grande do Norte, Brasil

Abstract: A salsicha é um embutido cárneo altamente comercializado e consumido pela população brasileira. Contudo, a alta manipulação durante o processamento aumenta os riscos de contaminação, sendo necessário a investigação da qualidade para verificar se o alimento está apto para o consumo humano. Assim, objetivou-se avaliar a qualidade físico-química e microbiológica de salsichas do tipo hot dog comercializadas no município de Mossoró, Rio Grande do Norte, Brasil. As amostras foram selecionadas e adquiridas em superme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…No microorganisms were found the artisan sausages; however, it is essential to note that the product quality could be affected by the inclusion of flour, as well as its starch content, due to the presence and increment of mold and yeasts, given that these microorganisms use starch as a growth substrate [63]. Macedo et al [64] reported counts of molds and yeast between 2.78 to 4.41 log CFU/g in hot dog sausages; these results were attributable to the pH, high water activity, and nutrient composition [65]. Likewise, Nkekesi et al [66] reported fungal counts ranging from 0.0 CFU/g to 9.83 × 10 3 CFU/g for street-vended grilled beef sausages.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…No microorganisms were found the artisan sausages; however, it is essential to note that the product quality could be affected by the inclusion of flour, as well as its starch content, due to the presence and increment of mold and yeasts, given that these microorganisms use starch as a growth substrate [63]. Macedo et al [64] reported counts of molds and yeast between 2.78 to 4.41 log CFU/g in hot dog sausages; these results were attributable to the pH, high water activity, and nutrient composition [65]. Likewise, Nkekesi et al [66] reported fungal counts ranging from 0.0 CFU/g to 9.83 × 10 3 CFU/g for street-vended grilled beef sausages.…”
Section: Microbiological Analysismentioning
confidence: 99%